Efficiency and Productivity of Italian Tourist Destinations: A Quantitative Estimation based on Data Envelopment Analysis and the Malmquist Method - Maria Francesca Cracolici; Peter Nijkamp (Tinbergen Institute, 2006)
This paper aims to provide a statistical analysis of the relative economic performance of Italian tourist areas. It uses two modelling approaches to estimate the competitiveness of these regions, viz. data envelopment analysis (DEA) and the Malmquist method. Our results show that the competitiveness position of several Italian regions has not improved over the years under consideration.
Keywords: L83; 330; competitiveness; Italian tourist industry; envelopment analysis